2014
DOI: 10.3747/pdi.2012.00109
|View full text |Cite
|
Sign up to set email alerts
|

Exit-Site Infection of Peritoneal Catheter is Reduced by the Use of Polyhexanide. Results of a Prospective Randomized Trial

Abstract: ♦ Background: One of the most common and severe complications affecting peritoneal dialysis (PD) patients is exit-site infection of the peritoneal catheter; it is therefore of vital importance to prevent it. This complication has a negative impact on the success of the technique. In spite of this, there are no clear guidelines concerning how to take care of the exit site. The objective of this study was to assess the efficacy of polyhexanide in preventing exit-site infection over a 12-month period. ♦ Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…A small randomized trial reported that topical application of 3% hypertonic saline is as effective as topical mupirocin cream for the prevention of ESI (130). Another study reported that topical polyhexanide resulted in a lower incidence of ESI than povidone-iodine (131). In contrast, topical polyhexamethylene biguanide was inferior to mupirocin in another randomized controlled trial, which was terminated after interim analysis (132).…”
Section: Topical Antibacterial and Antiseptic Agentsmentioning
confidence: 99%
“…A small randomized trial reported that topical application of 3% hypertonic saline is as effective as topical mupirocin cream for the prevention of ESI (130). Another study reported that topical polyhexanide resulted in a lower incidence of ESI than povidone-iodine (131). In contrast, topical polyhexamethylene biguanide was inferior to mupirocin in another randomized controlled trial, which was terminated after interim analysis (132).…”
Section: Topical Antibacterial and Antiseptic Agentsmentioning
confidence: 99%
“…Peritonitis remains a major problem in PD, with a substantial percent of patients developing persistent or relapsing infections [4]. To diagnose peritonitis it is important to observe and care for the catheter exit site [5]. In our study the participants' knowledge about diagnosis of peritonitis was deficient prior to our educational program and this improved significantly (P = 0.006) post intervention ( Table 2).…”
Section: Discussionmentioning
confidence: 79%
“…Catheter and exit-site care are of paramount importance in PD care [5] , [14]. Our nurses' sample needed a lot of education and training in this aspect before attaining significant improvement ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Overall fewer exit-site infections were observed in the polyhexanide group than in the povidone–iodine group, and this result was statistically significant ( P = 0.03). In conclusion, more robust and adequately powered studies are needed to be able to draw conclusive statements about the effectiveness of polyhexanide as a prophylactic agent against S. aureus infections 70 …”
Section: Resultsmentioning
confidence: 99%